2014
DOI: 10.4236/me.2014.54031
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Organic Cherry Farmers’ Strategies under Different Policy Options

Abstract: Organic farming has experienced a vast increase within the EU. Especially in Greece, the rapid growth of the organic sector, since the early '90s, was accompanied by the introduction of various organic crops. Among them, organic fruit crops have been gradually introduced, as farmers have realised the promising growth of the demand for organic fruits. However, organic farmers face significant yield and price risks, which combined with the high initial establishment costs, provoke difficult investment decisions.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…A "Sociedad Agraria de Transformación" is a cooperative-type association of independent farmers with both economic and social objectives, and to which the totality of the production of the farmers is allocated. Since the further exploitation of conventional varieties was deemed economically unfeasible, the diversification into higher-value crops was considered the best alternative for the majority of the small and medium-sized farms of the district as a means to guarantee not only the socio-economic feasibility of the holdings, but also the reform of the sector in line with a climate-smart agricultural approach [7].…”
Section: Introductionmentioning
confidence: 99%
“…A "Sociedad Agraria de Transformación" is a cooperative-type association of independent farmers with both economic and social objectives, and to which the totality of the production of the farmers is allocated. Since the further exploitation of conventional varieties was deemed economically unfeasible, the diversification into higher-value crops was considered the best alternative for the majority of the small and medium-sized farms of the district as a means to guarantee not only the socio-economic feasibility of the holdings, but also the reform of the sector in line with a climate-smart agricultural approach [7].…”
Section: Introductionmentioning
confidence: 99%
“…The result demonstrates that receiving subsidies is the most significant positive influence on farmers' decisions. Moreover, similar studies found a positive relationship between the conversion process as an institutional factor [66,67]. This revealed that the subsidy can be considered as a key factor to encourage farmers to convert to EFF and expand arable land area of EFF [68].…”
Section: Factors Influencing the Adoption Of Partially Converted Farmmentioning
confidence: 79%
“…Organic, high-quality products constitute an important aspect of Greek agriculture; given that Greek farmers are increasingly near the epicenter of a new ‘production model’ for Greece, policy-makers should provide necessary institutional support to organic farming by implementing the anticipated new CAP measures in a timely and cautious manner. Such initiatives should also couple the necessary institutional and legal improvements within the domestic supply chain in order to increase the market potential of organic products 26 , 43 , 44 . The creation of a meaningful value chain based on organic output of high quality is considered essential in order to put a dynamic part of the Greek agricultural sector on a sustainable and profitable future and to satisfy at the same time consumers’ concerns and access to foods of high nutritional value.…”
Section: Discussionmentioning
confidence: 99%